A recepção crítica de Nicanor Parra no Chile (1937- 2010) - Toro Castillo, Juan Francisco (Universidade Federal de São Carlos, 2016)
In this study we articulate and analyze Nicanor Parra’s critical fortune, published in Chile before and after the success achieved by the Chilean writer, having as parameter the Chilean National Prize of Literature, which he won in 1969. We point out to the reception aspects registered by real readers, that give life and dictate the history of Nicanor Parra’s literary Project, by taking over te text. Such critical impressions took place between 1939 and 2011. We observed the Horizon of Change passing through the critical fortune collected, by Robert Jauss Reception Theory.
Keywords: Recepção crítica; Nicanor Parra; Literatura; Teoria da estética da recepção; Robert Jauss; Reception Theory; Critical fortune; Historicity; Anti-poetry; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA